(untitled) (University Heart Journal, 2026)
Background: Congenital heart disease (CHD) represents a diverse group of structural cardiac abnormalities present from birth and is increasingly encountered in women of reproductive age. Maternal and neonatal outcomes during pregnancy vary widely according to lesion complexity, ventricular function, pulmonary pressures, and prior repair status, highlighting the need for careful risk assessment and multidisciplinary care. Objectives: To evaluate maternal and neonatal outcomes in pregnant women with CHD and compare outcomes between repaired and unrepaired lesions, and between simple and complex defects. Methods: This prospective observational study was conducted at Bangladesh Medical University from January 2024 to December 2025. Thirty-three pregnant women with confirmed CHD and singleton viable pregnancies were enrolled. Lesions were categorized as simple acyanotic, acyanotic with additional lesions, combined septal defects, or complex CHD, and stratified as repaired or unrepaired. Maternal outcomes included cardiac complications and death. Neonatal outcomes included birth weight, fetal growth restriction (FGR), NICU admission, and early neonatal death. Data were analyzed descriptively. Results: Simple acyanotic CHD predominated (63.6%); 33.3% had repaired and 66.7% had unrepaired lesions. Among 33 births, 42.4% were normal birth weight, 27.3% low birth weight, and 15.2% very low birth weight (all in the unrepaired group). Two maternal (6.1%) and two neonatal deaths (6.1%) occurred, exclusively in women with unrepaired CHD. FGR (12.1%) and NICU admissions (12.1%) were observed only among unrepaired cases. Conclusions: Pregnancy outcomes were more favorable in women with repaired, simple CHD. Unrepaired disease was associated with higher maternal and neonatal morbidity and mortality, highlighting the importance of pre-pregnancy counseling, timely intervention, and multidisciplinary care. University Heart Journal 2026; 22(1): 15-20